To the 110th anniversary of Academician D.D. Yablokov (1896—1993) - R. S. Karpov (Бюллетень сибирской медицины)
The article presents the understanding of scientific heritage of the prominent Russian clinician, founder of the Siberian school of physicians, Academician D.D. Yablokov, whose 110th jubilee took place on November of 2006.